Effect of cytosine and adenine on graphene oxide for the sensing of dopamine: Electrochemical and theoretical studies - Zhao, Yulin; Kumar, Mohan; Freiberger, Markus; Kudur Jayaprakash, Gururaj; Wang, Miao; Reddy, Sathish; Yang, Chenxin; Zhao, Wei (Microchemical Journal, 2024)
In this work, the electrochemical interaction between dopamine and cytosine/adenine on the graphene oxide (GO) is elucidated by quantum chemical simulation methods. Initially, GO, cytosine-functionalized GO (CGO), and adenine-functionalized GO (AGO) were prepared, and then utilized for the carbon paste electrode (CPE) modification. The as-prepared CGO-modified CPE (CGCPE) and AGO-modified CPE (AGCPE) were applied for the electrochemical sensing of dopamine (DA), and the obtained consequences illustrate the improved sensitivity of modified CPEs (MCPEs) compared to bare CPE (BCPE). Here, applied theoretical concepts based on analytical Fukui functions and frontier molecular orbitals (FMO) for cytosine and adenine functional groups in order to find active sites, and explained with evidence for the detection of DA by enhancing sensitivity. Moreover, the AGCPE has been shown higher electrochemical response compared to CGCPE for the detection of DA, and this result also agreed with theoretically from Global electron transfer results. The MCPEs were also utilized to examine the different electrochemical parameters and determine the DA concentration in the nanomolar range. The detection limit for CGCPE and AGCPE was found to be 9 nm and 7 nm, respectively.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Adenine; Cytosine; Dopamine; Frontier molecular orbitals; Graphene oxide